Relevance of gap junctions and large pore channels in traumatic brain injury - Prochnow, Nora (Frontiers in Physiology, 2014)
Abstract In case of traumatic brain injury (TBI), occurrence of central nervous tissue damage is frequently aligned with local modulations of neuronal and glial gap junction channel expression levels. The degree of gap junctional protein expression and intercellular coupling efficiency, as well as hemichannel function has substantially impact on the course of trauma recovery and outcome. During TBI, gap junctions are especially involved in the intercellular molecule trafficking on repair of blood vessels and the regulation of vasomotor tone. Furthermore, gliosis and astrocytic swelling due to mechanical strain injury point out the consequences of derailed gap junction communication. This review addresses the outstanding role of gap junction channels in TBI pathophysiology and links the current state of results to applied clinical procedures as well as perspectives in acute and long term treatment options.